On a comparison of the variance estimates of exponential distribution by multiple criteria decision making method - Satinee Lertprapai (2018)
In this paper, we consider the problem of estimation of the variance, θ 2 in one parameter exponential distribution when a prior point estimate of the variance is available. We compare five estimators of the variance, including class of four shrinkage estimators and one shrinkage estimator. The estimators of θ 2 are compared based on the Multiple Criteria Decision Making (MCDM) procedure in order to rank the estimators from the best to the worst in terms of their mean squared errors and to obtain the best estimator. © 2012 - IOS Press and the authors. All rights reserved.